The daughters of Zelophehad : a Nigerian perspective on inheritance of land by women according to Numbers 27:1-11 - Ahiamadu, Amadi (Stellenbosch : Stellenbosch University, 2012)
Thesis (MTh)--Stellenbosch University, 2005.